2020
DOI: 10.7196/samj.2020.v110i5.14221
|View full text |Cite
|
Sign up to set email alerts
|

The training of healthcare professionals: An expense or an investment?

Abstract: Many South Africans living in rural areas do not have access to affordable, quality, comprehensive healthcare, despite considerable government investments in programmes to strengthen the healthcare system. In their study, Pillay et al. [1] found that the burden of poverty and disease in South Africa (SA) is highest in rural areas, while Benatar et al. [2] confirmed that public and private health resources are skewed towards urban areas. Within the context of free primary health services, substantial barriers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…For instance, South Africa's public health sector has 0.64 anaesthetists per 100,00 population, compared to 9.69 in the private health sector whereas the country only needs 5 per 100,000 population [5]. The country's public health sector also only has 33 per 100,000 medical practitioners compared to a global average of 176 per 100,000 population [5][6][7]. Similarly, public sector primary care facilities are only serviced by 29.1% of the required professional nurses and midwives [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, South Africa's public health sector has 0.64 anaesthetists per 100,00 population, compared to 9.69 in the private health sector whereas the country only needs 5 per 100,000 population [5]. The country's public health sector also only has 33 per 100,000 medical practitioners compared to a global average of 176 per 100,000 population [5][6][7]. Similarly, public sector primary care facilities are only serviced by 29.1% of the required professional nurses and midwives [5].…”
Section: Introductionmentioning
confidence: 99%
“…Cuba with an agreement that after their training, they will return to serve their provinces for a specified period of time [13,14]. Some NGO RoS schemes like the Umthombo Youth Development Foundation [6,15] and the Friends of Mosvold Scholarship scheme [16,17] have previously been reported on in more detail and found the schemes to have a good return on investment [6,[15][16][17]. However, to date, there is little literature scrutinising the challenges, implementation process and sustainability of the government sponsored schemes [4,13,[16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Where FP posts do not yet exist, tertiary or regional posts may be well repurposed and deployed to district level to facilitate this process. Finally, to extend an existing model, 2 – recruiting candidates from rural communities for later inclusion in local FP programmes might present exciting prospects.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that attrition rates in health professional programs are a concern, with factors such as academic difficulty, financial challenges, and personal circumstances contributing to dropout rates [20]. However, initiatives like student support programs and curriculum reforms aim to improve retention and graduation rates while aligning with the country's healthcare needs [21].…”
Section: Introductionmentioning
confidence: 99%